# |
ODE |
Mathematica |
Maple |
\[
{}2 t y^{\prime \prime }+\left (t +1\right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 t^{2} y^{\prime \prime }-t y^{\prime }+\left (t +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 t y^{\prime \prime }+3 y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}2 t^{2} y^{\prime \prime }+\left (t^{2}-t \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{3} y^{\prime \prime }-t y^{\prime }-\left (t^{2}+\frac {5}{4}\right ) y = 0
\] |
✓ |
✗ |
|
\[
{}t^{2} y^{\prime \prime }+\left (-t^{2}+t \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }-\left (t^{2}+2\right ) y^{\prime }+t y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+\left (-t^{2}+3 t \right ) y^{\prime }-t y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t \left (t +1\right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }-\left (t +4\right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+\left (t^{2}-3 t \right ) y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }-\left (t +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }+t y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }+\left (-t^{2}+1\right ) y^{\prime }+4 t y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+t^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t^{2}-v^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }+\left (1-t \right ) y^{\prime }+\lambda y = 0
\] |
✓ |
✓ |
|
\[
{}2 \sin \left (t \right ) y^{\prime \prime }+\left (1-t \right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }+y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-t \left (t +1\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t^{2}-1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }+3 y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-t y = 0
\] |
✓ |
✓ |
|
\[
{}\left (t^{2}+2\right ) y^{\prime \prime }-t y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-t^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}t \left (2-t \right ) y^{\prime \prime }-6 \left (t -1\right ) y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+t^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-t^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left (t^{2}+2 t +1\right ) y^{\prime }-\left (4+4 t \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 t y^{\prime }+\lambda y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+\alpha \left (\alpha +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-t^{2}+1\right ) y^{\prime \prime }-t y^{\prime }+\alpha ^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+t^{3} y^{\prime }+3 t^{2} y = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}\left (1-t \right ) y^{\prime \prime }+t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+t y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+t y^{\prime }+{\mathrm e}^{t} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+{\mathrm e}^{t} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+{\mathrm e}^{-t} y = 0
\] |
✓ |
✓ |
|
\[
{}t \left (t -2\right )^{2} y^{\prime \prime }+t y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t \left (t -2\right )^{2} y^{\prime \prime }+t y^{\prime }+y = 0
\] |
✓ |
✗ |
|
\[
{}\sin \left (t \right ) y^{\prime \prime }+\cos \left (t \right ) y^{\prime }+\frac {y}{t} = 0
\] |
✓ |
✓ |
|
\[
{}\left ({\mathrm e}^{t}-1\right ) y^{\prime \prime }+{\mathrm e}^{t} y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-t^{2}+1\right ) y^{\prime \prime }+\frac {y^{\prime }}{\sin \left (t +1\right )}+y = 0
\] |
✓ |
✗ |
|
\[
{}t^{3} y^{\prime \prime }+\sin \left (t^{2}\right ) y^{\prime }+t y = 0
\] |
✓ |
✓ |
|
\[
{}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-\left (t +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 t y^{\prime \prime }+\left (1-2 t \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 t y^{\prime \prime }+\left (t +1\right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 t^{2} y^{\prime \prime }-t y^{\prime }+\left (t +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 t y^{\prime \prime }+3 y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}2 t^{2} y^{\prime \prime }+\left (t^{2}-t \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-t y^{\prime }-\left (t^{2}+\frac {5}{4}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+\left (-t^{2}+t \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }-\left (t^{2}+2\right ) y^{\prime }+t y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+\left (-t^{2}+3 t \right ) y^{\prime }-t y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t \left (t +1\right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }-\left (t +4\right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+\left (t^{2}-3 t \right ) y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }-\left (t +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }+t y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+\left (-t^{2}+1\right ) y^{\prime }+4 t y = 0
\] |
✓ |
✗ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+t^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t^{2}-v^{2}\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }+\left (1-t \right ) y^{\prime }+\lambda y = 0
\] |
✓ |
✓ |
|
\[
{}t \left (1-t \right ) y^{\prime \prime }+\left (\gamma -\left (\alpha +\beta +1\right ) t \right ) y^{\prime }-\alpha \beta y = 0
\] |
✓ |
✓ |
|
\[
{}2 \sin \left (t \right ) y^{\prime \prime }+\left (1-t \right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t +1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }+y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }-t \left (t +1\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t^{2}-1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}t y^{\prime \prime }+3 y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}t^{2} y^{\prime \prime }+t p \left (t \right ) y^{\prime }+q \left (t \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {1-y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x y-x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x +\frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \ln \left (x y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x y+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (x \right )+\sin \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \sin \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {{y^{\prime }}^{2}}{2}-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \sin \left (x y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \cos \left (x y\right )
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime \prime }+5 y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}3 x \left (3 x +2\right ) y^{\prime \prime }-4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (x +4\right ) y^{\prime \prime }+7 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+\left (-x^{2}+x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+5 x y^{\prime }+\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}9 x^{2} y^{\prime \prime }+\left (3 x +2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+2 x^{2}\right ) y^{\prime \prime }-x y^{\prime }+\left (1-x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-3 \left (x^{2}+x \right ) y^{\prime }+\left (3 x +2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{\prime \prime }+\left (-x^{2}+5 x \right ) y^{\prime }+\left (2 x^{2}-1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+x \left (x^{2}-4\right ) y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }-3 \left (x^{2}+x \right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|